Combined Near-Infrared Spectroscopy and Intravascular Ultrasound Imaging of Pre-Existing Coronary Artery Stents: Can Near-Infrared Spectroscopy Reliably Detect Neoatherosclerosis?. (January 2016) - Madder, Ryan D.; Khan, Mohsin; Husaini, Mustafa; Chi, Margaret; Dionne, Sarah; VanOosterhout, Stacie; Borgman, Andrew; Collins, J. Stewart; Jacoby, Mark
Abstract : Background—: Neoatherosclerosis is an emerging phenomenon in which lipid-rich plaques (LRPs) develop within pre-existing stents. This study was undertaken to describe near-infrared spectroscopy (NIRS) and intravascular ultrasound findings in pre-existing stents and to compare NIRS findings in pre-existing stents, in which an increased lipid signal has been speculated to indicate neoatherosclerosis, and NIRS findings in a control group of freshly implanted stents, in which any lipid signal originates from fibroatheroma under the stent. Methods and Results—: At the site of LRP detected by NIRS in a cohort of pre-existing stents, intravascular ultrasound was used to determine the presence of neointimal tissue. The lipid-core burden index and maximum lipid-core burden index in 4 mm were measured within stented segments. Findings were compared between pre-existing stents and a control group of freshly implanted stents. Among 60 pre-existing stents implanted 5.5±4.0 years earlier, NIRS detected LRP in 33%. At the site of LRP, intravascular ultrasound found no neointimal tissue in 35% of cases. NIRS findings in pre-existing stents were indistinguishable from those of freshly implanted stents (lipid-core burden index: 50±72 versus 42±58; P =0.40 and maximum lipid-core burden index in 4 mm: 156±184 versus 155±203; P =0.69). Conclusions—: The detection of LRP in a pre-existing stent by NIRS alone is not reliable evidence of neoatherosclerosis, as the lipid signal may originate from fibroatheroma underlying the stent. By identifying the presence or absence of neointimal tissue at the site of LRP detected by NIRS, intravascular ultrasound may provide some insight into the potential source of the lipid signal in pre-existing stents. Registration Information—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01694368.